Diagnostic value of non-invasive indicators of myocardial function in patients after myocardial infarction - V. E. Oleynikov; A. V. Shcherbinina; A. V. Golubeva; V. A. Galimskaya; O. D. Vershinina (Российский кардиологический журнал, 2024)
Aim. To study the diagnostic value of myocardial function parameters to assess their predictive ability in relation to left ventricular (LV) global contractility in patients after myocardial infarction (MI).Material and methods. The final analysis included 97 patients with MI aged 55,9±8,6 years. We performed standard two-dimensional echocardiography and speckle tracking echocardiography with analysis of following myocardial function parameters: global work index (GlobalWI, mm Hg %); global constructive work (GlobalCW, mm Hg %); global wasted work (GlobalWW, mm Hg %); global work efficiency (GlobalWE). The probability of ejection fraction (EF) reduction was analyzed using ROC curves using three criteria. The function parameters with the maximum sum of sensitivity and specificity were selected as the cut-off point.Results. On days 7-9 after MI, depending on the EF, patients were divided into 3 groups: "REF" — patients with EF <40%); "MREF" — with EF from 40 to 49%, and "PEF" — patients with EF ³50%. By the 24th week, GlobalWI increased by 23% in the PEF group and by 33% in the MREF group. In the REF group, there was a gradual decrease in GlobalWI until the end of the study. In the PEF group, GlobalCW increased by 21% by week 24. By the end of follow-up, an increase in GlobalWW of 15% was observed in the REF group. GlobalWI, GlobalCW and GlobalWW were found to have the highest sensitivity values (60%) for reduced EF, ranging from 4049% at 24 weeks from the index event. GlobalWW had the highest specificity value (80%). With regard to a decrease in EF <40% by week 24, the GlobalWW had the highest sensitivity (50%) and specificity (70%).Conclusion. Parameters of myocardial function have diagnostic and prognostic value for assessing LV systolic function after MI. Already in the acute period, myocardial function parameters can be used to determine the risk of decreased LV global contractility.